Nuclear Oncology : From Pathophysiology to Clinical Applications - Strauss, H. William; Mariani, Giuliano; Volterrani, Duccio; Larson, Steven M. (Springer International Publishing : Imprint: Springer, 2017)
This book discusses the role of nuclear medicine in the diagnosis, staging, and treatment of patients with specific cancers. It presents the incidence, pathophysiologic and clinical aspects of the disease, the use of nuclear imaging in diagnosis, staging requirements, management of specific tumors, and surveillance after primary treatment of cancers. It addresses the various diagnostic/therapeutic options that are currently available or are most likely to become available in the near future according to a prioritized approach, thereby keeping to a minimum the number of diagnostic imaging procedures the patient is expected to undergo. Topics include basic science, clinical applications, radionuclide therapy, radioguided surgery, heart disease in the cancer patient, and adverse effects of cancer therapy. Each clinical chapter discusses the radionuclide procedures within an integrated framework, thereby identifying the information required for effective treatment of specific tumors. The book concludes with a series of cases that define and expand the didactic material in the clinical application chapters. Thoroughly updated and revised, the second edition incorporates advances in imaging and therapy and features the current staging guidelines of the American Joint Committee on Cancer. With contributions from a group of internationally distinguished practitioners, Nuclear Oncology: From Pathophysiology to Clinical Applications, Second Edition, is a valuable reference for nuclear medicine physicians, radiologists, medical and surgical oncologists, and other clinicians involved in the care and management of cancer patients.
Keywords: Medicine.; Nuclear medicine.; Oncology.; elektronické knihy; electronic books